2018
DOI: 10.1002/jrs.5506
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐patterned microarray chips for ultrasensitive surface‐enhanced Raman scattering detection of ultratrace samples

Abstract: This paper reports the fabrication of gold‐patterned microarray chips for fast and ultrasensitive surface enhanced Raman scattering (SERS) detection of trace samples. By micro‐nano machining based on electron‐beam lithography, magnetron sputtering, and chemical modification, gold‐patterned microarray chips with hydrophilic and hydrophobic periodic structures are fabricated, and a polyethylene glycol (PEG) layer is coated on the surface of the gold well, making the chips long‐term stable. The hydrophilic surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Their results indicate that the 4‐methylthiophenol‐ and thiophenol‐modified substrates do not exhibit significant SERS enhancement, resulting in intensity being dependent on distance. Chen et al [ 17 ] reported the fabrication of gold‐patterned microarray chips for fast ultrasensitive SERS detection of trace samples. They conclude that such gold‐patterned microarray chips are promising for SERS detection of various chemical and biological species, such as only 0.3 μl in the detection of malachite green, 4‐mercaptopyridine, rhodamine 6G, and melamine, with the detection limits reaching the nm.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…Their results indicate that the 4‐methylthiophenol‐ and thiophenol‐modified substrates do not exhibit significant SERS enhancement, resulting in intensity being dependent on distance. Chen et al [ 17 ] reported the fabrication of gold‐patterned microarray chips for fast ultrasensitive SERS detection of trace samples. They conclude that such gold‐patterned microarray chips are promising for SERS detection of various chemical and biological species, such as only 0.3 μl in the detection of malachite green, 4‐mercaptopyridine, rhodamine 6G, and melamine, with the detection limits reaching the nm.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS), as a rapid response, high sensitivity, and fingerprint effect spectroscopy technique, has been most intensively exploited in many areas of the trace detection of analytes, biological analysis, medical detection, and other molecule level identification applications. At present, the more widely used surface-enhanced Raman substrates are noble-metal colloids due to their superior surface-enhanced Raman performances. Unfortunately, as for them, there are also various disadvantages such as harsh preparation conditions, residual surfactant or surface protective reagent interference, and easy aggregation during use and storage. , Gradually, some physical methods like electron-beam lithography, focused ion-beam lithography, photolithography, and so on have been developed to overcome the shortcomings of the colloidal chemistry methods. These methods can produce nanostructures with precise size, regular shape, and uniform hot spot distribution. However, such methods suffer from small sample volume, high cost, and complex instrumentation, which are very unfavorable for the future practical application of the substrates.…”
Section: Introductionmentioning
confidence: 99%